2023
DOI: 10.1097/01.jaa.0000911216.02925.52
|View full text |Cite
|
Sign up to set email alerts
|

Whither the PA doctorate?

Abstract: New perspectives have been brought to bear in the discussion of the topic of the physician associate/assistant (PA) doctoral degree in general and the entry-level PA doctorate in particular. Both the Physician Assistant Education Association (PAEA) and the American Academy of Physician Associates (AAPA) have sought and supported formal research investigations into the question. Evidence from studies shows that perceived benefits and risks are strongly influenced by the lens of the various stakeholders; that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Few PAs in the professoriate have the training and experience they need to conduct research and writing. 3,5,13 While PAs traditionally enter the profession to deliver patient care, academia requires them to acquire a different skill set. 14,15 Evidence-based medicine and the ability to critically evaluate scientific literature became an accreditation requirement of PA curricula relatively recently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few PAs in the professoriate have the training and experience they need to conduct research and writing. 3,5,13 While PAs traditionally enter the profession to deliver patient care, academia requires them to acquire a different skill set. 14,15 Evidence-based medicine and the ability to critically evaluate scientific literature became an accreditation requirement of PA curricula relatively recently.…”
Section: Introductionmentioning
confidence: 99%
“…In the PA profession, the education of our senior educators—who in other professions act as mentors and inspire and sponsor junior faculty—took place well before the teaching of research methods. 13 Thus, few PAs have the required training, and many of our professional “elders” often lack the skills needed to develop the next generation of researchers. To compound the problem, PA educators are pursuing doctoral-level degrees at rates higher than previously reported in the literature, 16 yet many doctoral candidates are pursing clinical degrees that do not emphasize research methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PA programs have transitioned from a bachelor to a master's level degree, the faculty education has decreased slightly, with current reports showing 24% of PA faculty have doctoral degrees, compared with 29% in 2010 and 2017 8,11. An increasing number of PAs have a master of public health degree, but few of these PAs are involved in research 2. Some PA educators express a lack in their own training about research, which creates obstacles to leading student research projects 12.…”
mentioning
confidence: 99%
“…Articles with recommendations to improve PA or health professions research showed three main domains of support: material support, educational support, and social support 2,4,6,8,12-15…”
mentioning
confidence: 99%